Umbilical Cord Separation Time and Influencing Factors in Very-Low-Birth-Weight Preterm Neonates - Unal, Sezin; Demirel, Nihal; Arslan, Zehra; Tokgoz-Cuni, Betül; Ulubas-Isik, Dilek; Bas, Ahmet Yagmur (American Journal of Perinatology, 2021)
Objective The average time for umbilical cord separation in term neonates is 7 to 10 days. Prematurity, phototherapy, prolonged duration of antibiotic treatment, and parenteral nutrition are other factors which were demonstrated to delay cord separation. In the previous studies including greater premature infants, the time of separation of the umbilical cord was shown to vary 2 to 3 weeks. We aimed to determine the cord separation time and associated factors in very-low-birth-weight (VLBW) infants.Study Design In this retrospective study, VLBW infants (birth weight [BW] <1,500 g, gestational age [GA] < 32 weeks) without umbilical catheterization were included. Specific cord care was not applied. The cord separation time, gender, mode of delivery, presence of sepsis, duration of antibiotic treatment, serum free thyroxine, free triiodothyronine (FT3), thyroid-stimulating hormone, lowest leukocyte, polymorphonuclear leukocytes (PMNLs), and platelet counts were recorded.Results The study included 130 infants (GA: 29 ± 2 weeks, BW: 1,196 ± 243 g). Mean cord separation time was 14 ± 5 days, while 95th percentile was 22nd day of life. A positive correlation was demonstrated between duration of antibiotic treatment and cord separation time (p < 0.001, r: 0.505). Cord separation time did not differ regarding gender or mode of delivery. Corrected leukocyte count (p = 0.031, r: −0.190) and PMNL count (p = 0.022, r: −0.201), and serum FT3 level (p = 0.003, r: −0.261) were found to be negatively correlated with cord separation time. The cord separation time was found to be delayed in the presence of sepsis (with sepsis: 18 ± 7 days and without sepsis: 13 ± 3 days; p = 0.008). Sepsis was found to delay the cord separation time beyond second week (odds ratio = 6.30 [95% confidence interval: 2.37–15.62], p < 0.001).Conclusion The 95th percentile for cord separation time was 22nd day. Sepsis might be either the reason or the consequence of delayed cord detachment. The exact contribution of low serum FT3 levels to the process of cord separation should be investigated in further studies.Key Points
Keywords: premature infants; umbilical cord separation; sepsis; intensive care